2021
DOI: 10.3389/fcimb.2021.688989
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Bacterial Characteristics of Klebsiella pneumoniae Affecting 30-Day Mortality in Patients With Bloodstream Infection

Abstract: BackgroundThere is a paucity of studies using clinical characteristics and whole-genome sequencing together to fully identify the risk factors of patients with Klebsiella pneumoniae (KP) bloodstream infection (BSI).MethodsWe retrospectively analyzed the clinical and microbiological characteristics of patients with KP BSI. Isolates were processed using Illumina NGS, and relevant bioinformatics analysis was conducted (multi-locus sequence typing, serotype, phylogenetic reconstruction, detection of antibiotic res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 47 publications
3
8
0
Order By: Relevance
“…2 Wu et al demonstrated that more than 36 STs were established in 79 BSI K. pneumoniae strains. 27 This study revealed that hvKP strains were more susceptible to tested antibiotics than cKP, consistent with previous studies. 1,8,10 The confluence of hypervirulence and multidrug resistance, especially carbapenem resistance, is extremely alarming.…”
Section: Discussionsupporting
confidence: 92%
“…2 Wu et al demonstrated that more than 36 STs were established in 79 BSI K. pneumoniae strains. 27 This study revealed that hvKP strains were more susceptible to tested antibiotics than cKP, consistent with previous studies. 1,8,10 The confluence of hypervirulence and multidrug resistance, especially carbapenem resistance, is extremely alarming.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, p537-20_1 also carried the iutA gene encoding the receptor of aerobactin, which is an important virulence factor for ExPEC and hypervirulent K. pneumoniae [ 52 ]. The carriage of iutA has been shown to be associated with increased mortality in E. coli , as well as K. pneumoniae bloodstream infection [ 23 , 64 ]. The possession of the iutA gene but also many other iron acquisition genes likely represents a fitness advantage in the biliary tract, due to the general iron limitation in bile [ 23 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the capsule-associated genes wabG (encoding capsule), uge (encoding capsule lipoprotein), ycfM (promoting external membrane protein), ureA (urease) are highly involved in virulence on account of their ability to evade phagocytosis and complement-mediated killing and further inhibit complement activation of the host. 39 , 40 CPS-associated genes (cps, ctrD, wcb, wzt, ureA) were detected in three strains. Moreover, the results of the serum resistance assay in our study revealed thatstrain 2 showed resistance, while strains 1 and 3 showed sensitivity.…”
Section: Discussionmentioning
confidence: 99%